Sistema informático para la gestión de la evaluación de desempeño de los docentes en la Universidad Técnica de Cotopaxi - Muyulema Andrade, Wilmer David (2017)
The present research is due to the request which was sent by the management of the Technical University of Cotopaxi (UTC) of a system that allows students and coordinators of the career to manage the information about assessment of the professors who work at the university. Besides, nowadays the university doesn’t have this tool which allow to do this activity. This research aims to contribute a computer system for the assessment of the professors’ performance at Cotopaxi Technical University. So the system will allow students to evaluate them through the Internet. The system will also allow of the career to evaluate their professors obtaining the register of the information to be analyzed by the management at any moment. With installation of this computer system for the management of the information. The management and students of Cotopaxi Technical University will be benefit. The system has a direct impact on the process of performance assessment of the professor’s Cotopaxi Technical University. In the practice, the system has the advantage of streamlining this process allowing students to evaluate anonymously, this means that professors won’t know the result that they get from their students. This information could be consulted by management of Cotopaxi Technical University or the systems administrator.